A integração das TIC no contexto do programa de aprendizagem no transporte: possibilidades e realizações - Barrero, Patrícia da Silva (2015)
This research, carried out in the Professional Master s of the Graduate Program in Networked Educational Technologies, in the research line Networked Educational Technologies Management, aims to investigate the integration of Networked Educational Technology (ICT) in training activities of the Learning Program in Transportation in order to contribute to the training of an employee profile of information society. It aimed to carry out practical actions that presented these technological tools as mediation resources in the educational process. The study was in the perspective of action research and, in the actions, we dealt with concepts involving work projects with emphasis on problem solving. Still, it had as categories of analysis the technological fluency and the autonomy of the subjects, the dropout rate of young learners and the teaching-learning process in the context. On the possibilities and achievements, the results indicate that the activities involving ICT contribute to students development and teachers update about the use of these resources, therefore enabling a favorable environment for contextual teaching and learning process and collaborating to the permanence of learners in the training course. As a product, we developed several microprojects based on Fernando Hernandéz Project Method.